Effects of air swirl on the combustion and emissions characteristics of a cylindrical furnace fueled with diesel-biodiesel-n-butanol and diesel-biodiesel-methanol blends. (15th May 2020) - Amiri, Mohsen; Shirneshan, Alireza
Abstract: In this research, the effects of air swirling on the emission and combustion characteristics of a cylindrical furnace fueled with various diesel-biodiesel-n-butanol and diesel-biodiesel-methanol blends were studied. The tests conducted on a burner with a radial air swirler and different vane angles (15°, 25°, 35°, 45°, 60°, and 90°) that was mounted to the combustion chamber. The results showed that the air swirler with vane angles of 35° and 60° can improve the CO and HC emission. Also, the CO2 and NOx emissions improved at the angles of 45° and 60°. The results indicated that the use of n-butanol and methanol as the mixture with diesel-biodiesel blends can improve the CO and HC emissions compared to neat diesel combustion. However, a five percent increase in methanol and butanol amount resulted in an increase (around 18%) in these pollutants. On the other hand, an increase in the percentage of alcohol in fuel mixture can reduce CO2 and NOx emissions up to 12%. According to the results, the mean temperature of combustion gas decreased about 2% in some points with the addition of n-butanol and methanol in the fuel mixture due to the small cetane number and lower heating value of these alcohols compared to diesel and biodiesel. The results indicated that air swirler with the vane angle of 60° had a better condition for the reduction of pollutants among other angles.